Correlation Analysis between Daily Routine Physical Activity and Blood Glucose Control in Diabetes Mellitus Patients at the Kampung Masjid Labuhan Batu Utara Community Health Center - Rahma Siregar; Henny Henny; Dewi Febrini (CV. Inara, 2025)
Elevated blood glucose and low physical activity represent critical health concerns in primary healthcare settings. This study aimed to analyze the correlation between daily routine physical activity and blood glucose control in patients with diabetes mellitus at Kampung Masjid Primary Health Center, North Labuhan Batu. A quantitative descriptive correlational design with cross-sectional approach was employed. Total sampling encompassed 55 diabetes patients meeting inclusion criteria. Data collection utilized the Global Physical Activity Questionnaire (GPAQ) and random blood glucose measurements from medical records. Spearman rank correlation analysis was conducted using SPSS version 25 following KolmogorovSmirnov normality testing. Results demonstrated a significant negative correlation (r = -0.615, p = 0.000) between physical activity levels and blood glucose concentration. Approximately 45.5% of patients engaged in low physical activity, while the mean blood glucose was 307.53 mg/dL, substantially exceeding therapeutic targets. Increased physical activity substantially improved glycemic control, indicating that physical activity represents a critical modifiable factor for diabetes management in primary healthcare. These findings support evidence-based physical activity promotion as essential for integrated diabetes management approaches combining pharmacological intervention with structured exercise supervision at Puskesmas facilities throughout Indonesia.